Intervensi PELINDUNG: Pencegahan ISPA Bagi Anak dan Remaja di LKSA Panti Asuhan Berkah Kota Palangka Raya, Kalimantan Tengah - Aloysia Ispriantari; Musthika Wida Mashitah (Institut Nalanda, 2026)
The high number of Acute Respiratory Infections (ARI) in Indonesia, driven by environmental factors and the vulnerability of the child population, is a serious concern. Children and adolescents in Child Welfare Institutions (LKSA) are at high risk due to crowded conditions and limited facilities. This community service activity aims to increase awareness and practice of ARI prevention among children at the LKSA Panti Asuhan Berkah Palangka Raya. The